Posidonia Natural Residues as Growing Substrate Component: An Ecofriendly Method to Improve Nutritional Profile of Brassica Microgreens - D’Imperio, Massimiliano; Montesano, Francesco Fabiano; Montemurro, Nicola; Parente, Angelo (Frontiers in Plant Science, 2021)
The aim of this study was to test Posidonia oceanica (L.) Delile seagrass residues (leaves and fibers) as growing media component to improve the nutritional quality of two different brassica microgreens (Mizuna and Rapini). We hypothesised that addition of posidonia residues in the substrate would result in higher concentration of certain mineral nutrients in the edible parts of plants. Substrates were obtained by mixing leaves and fibers, each material at the rate of 25, 50 and 75% (v/v), with a peat based commercial substrate, that was also used at 100% rate as a control treatment. Two experiments were carried out (Experiment 1: Mizuna microgreens production in growth chamber conditions; Experiment 2: Mizuna and Rapini microgreens production in greenhouse conditions). Plant growth measurements and chemical analysis on edible parts (mineral tissue composition and main bioactive compounds - polyphenol, chlorophylls and carotenoids contents) were performed in order to evaluate the effects of the different substrates on growth and nutritional composition of brassica microgreens. In order to evaluate the consumer safety, daily intake, percentage of recommended daily allowance for I (RDA-I) and hazard quotient (HQ) for I intake through consumption of 50 and 100 g portions of Rapini microgreens were calculated. Posidonia in the growing media mixtures increased I and B content in edible parts of microgreens. The calculated HQ underlines the safety of these products. Results confirm the possibility to improve nutritional profile of brassica microgreens by using this natural material as a growing media component, resulting in a sustainable approach.